KRITERIA KETUNTASAN CAPAIAN BELAJAR PADA KURIKULUM SMA EL FITRA KOTA BANDUNG - Ucu Marlina; Rusman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research is purposed to determine several criteria that indicate the completeness of learning outcomes in the curriculum at the secondary education level. These criteria will be used to determine the completeness of mastery of competencies through the stages of the evaluation process. The 22nd Episode Merdeka Curriculum Policy on Transformation of Selection for PTN encourages comprehensive learning, as well as multidisciplinary knowledge based on the interests of students at the secondary education level. The completeness of learning achievements in mastering competencies is known based on criteria in the affective, cognitive, and psychomotor domains. Therefore, the object of research involved 125 students who have had learning experiences at PTN. Based on the review of the KTSP document of El Fitra High School, the criteria for the completeness of learning outcomes that must be mastered by grade 12 students in preparation for higher education can be compiled. Analytical description with data collection through interviews, surveys, and document review are used as research methods. The results of the research are in the form of criteria in the completeness of learning outcomes in school education programs, implementation, and achievement of results. These criteria will be an indicator or instrument that can be used by counseling teachers (BK) in assisting learning achievement completeness and career guidance.